Analisis Pengaruh Citra Merek Institusi Pendidikan terhadap Keputusan Pendaftaran Siswa - Chairul Anwar; Widyatmike Gede Mulawarman (Journal on Education, 2025)
This study aims to analyze the influence of an educational institution's brand image on student enrollment decisions. A strong brand image can enhance institutional appeal and reduce prospective students' sensitivity to factors such as cost and location. This research employs a qualitative method with a literature review approach to identify key factors shaping brand image and how they influence student and parent choices. The analysis reveals that a positive brand image is influenced by academic quality, faculty reputation, facilities, and digital marketing strategies. Additionally, the impact of brand image varies across educational levels, where parents play a more dominant role in decision-making for elementary and middle schools, whereas prospective university students prioritize accreditation and alumni networks. This study provides insights for educational institutions to develop more effective and sustainable branding strategies. Further research is needed to understand how evolving trends and educational policies may impact brand image in the long term.